Crescimento da cebola em função de doses de nitrogênio, potássio e da população de plantas em semeadura direta - Filho, Arthur Bernardes Cecílio [UNESP]; May, André; Porto, Diego R. Q. [UNESP]; Barbosa, José Carlos [UNESP] (My University, 2009)
The effects of nitrogen and potassium fertilizer doses were evaluated on the growth of two onion cultivars, grown in different plant populations. The experiment was carried out in São José do Rio Pardo in an onion production area in São Paulo State, Brazil, from 03/07 to 08/08/04. The experimental design was of blocks with four replications in a 2×4×4×4 factorial cheme: cultivars (Hybrids Optima and Superex), nitrogen (0; 50; 100 and 150 kg ha-1 N), potassium (0; 75; 150 and 225 kg ha-1 K2O) and plant populations (60; 76; 92 and 108 plants m2). There was significant effect on the factors separately. At the end of the cycle, the cv. Optima presented larger quantities of dry matter in the aerial parts (APDM) and in the bulbs (BDM). The application of nitrogen promoted significant increments in APDM and BDM. The influence of K on APDM was not as expressive as in relation to that observed for the nitrogen, but similarly to this, it increased the accumulation of BDM. The increase of the population of plants reduced the APDM and consequently the BDM. The equations of accumulation of APDM and of BDM, of both cultivars, obtained as the response to the doses of N and K and population of plants, didn't differ from each other.
Accumulation of dry mass in onion depending on nitrogen, potassium and plant population in direct sowing
Keywords: Allium cepa L.; Cultivar; Fertilization; Plant density